Case Report: Successful Concomitant Pulmonary Thromboendarterectomy and Carotid Endarterectomy - Liu, Zhan; Liu, Xiaopeng; Zheng, Xia; Lin, Fan; Sun, Guang; Ye, Zhidong; Zhen, Yanan; Liu, Peng (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary thromboendarterectomy is the treatment of choice for chronic thromboembolic pulmonary hypertension. Pulmonary thromboendarterectomy concomitant with additional cardiac procedures was reported as safe and feasible. However, the treatment strategy for chronic thromboembolic pulmonary hypertension patients with severe carotid stenosis is still not clear. We describe a case of successful concomitant pulmonary thromboendarterectomy and carotid endarterectomy.